Oncogenic GOPC-ROS1 Fusion Identified in a Congenital Glioblastoma Case. Issue 8 (November 2020) - Whiteway, Susan L.; Betts, Aaron M.; O'Neil, Erika R.; Green, Adam L.; Gilani, Ahmed; Orr, Brent A.; Mathis, Derek A.
Abstract : Congenital glioblastoma (GBM) is a rare brain tumor of infancy. While histologically they resemble pediatric and adult GBM, growing evidence suggests a distinct molecular profile. We report the case of a 7-day-old infant female with congenital GBM found to harbor a GOPC-ROS1 fusion. She underwent surgical resection, moderate-intensity chemotherapy without radiation, and remains disease-free 4 years from completion of therapy. While the frequency of this mutation is not known, the identification of this oncogenic driver may provide insight into the pathogenesis of GBM in this age group and may serve as a molecular target for select patients.